Pengaruh Kualitas Pelayanan Terhadap Kepuasan Konsumen Pada Toko Fotocopy Givme Anugerah Tanah Periuk - Amir Hamzah; Hadijah Hadijah; Dini Suryaningsih (Jurnal Inovasi Manajemen, Kewirausahaan, Bisnis dan Digital, 2024)
The purpose of this research is to determine the influence of service quality consisting of reliability (X1), responsiveness (X2), guarantee (X3), empathy (X4), and tangibility (X5) on consumer satisfaction at the Givme Anugerah Tanah Periuk photocopy shop simultaneously and Partial. The respondents in this research were all consumers at the Givme Anugerah Photocopy Shop. Based on the results of the Validation Test on the 27 instruments used in this research, it is valid because rcount > rtable and the Reliability Test for the 27 instruments in this study can be relied on and remains consistent if the measurements are repeated or carried out at other times because Cronbach's Alpha > 0.6. The value of the regression equation is obtained Y = 2.092 – 0.047 X1 – 0.012 X2 – 0.135 X3 + 0.141 X4 + 0.542 The multiple correlation coefficient (R) value, namely 0.708, shows a strong influence between the Service Quality (X) variables which consist of Reliability (X1), Responsiveness (X2), Assurance (X3), Empathy (X4), and Tangibility (X5) simultaneously. on the variable Consumer Satisfaction (Y) at the Givme Anugerah Tanah Periuk Photocopy Shop. The value of the coefficient of determination (R2) obtained is 0.501, meaning that the variation in Service Quality (X) on Consumer Satisfaction (Y) is 50.1%. This can be interpreted that the contribution of the independent variable to the dependent variable is 50.1% and the remaining 49.9% is contributed by other variables not included in this research. In the F test, it is obtained that Fcount > Ftable (10.830 > 2.39) with a sig value of 0.000 at ɑ = 5% (0.05), so H0 is rejected and Ha is accepted. so it can be concluded that the hypothesis which states that the variables Reliability (X1), Responsiveness (X2), Guarantee (X3), Empathy (X4), and Tangibility (X5) influence simultaneously (simultaneously) on Consumer Satisfaction at the Givme Anugerah Tanah Photocopy Shop Stoneware is acceptable. Based on the t test, it is known that Form (X5) has a dominant influence on Consumer Satisfaction (Y) at the Givme Anugerah Tanah Periuk Photocopy Shop with a value of tcount > ttable or 4.643 > 1.673 with a significant level of 0.000, so it can be concluded that Form (X5) has a significant influence on Consumer Satisfaction (Y) then H0 is rejected and Ha is accepted.